2003
DOI: 10.1046/j.1399-0012.2003.00055.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemoembolization followed by orthotopic liver transplant for epithelioid hemangioendothelioma

Abstract: Hepatic epithelioid hemangioendothelioma (HEHE) is a rare liver tumor with an indolent course relative to other hepatic malignancies. Over the past two decades, primary treatment for these lesions has been defined as resection for localized disease, or transplantation for diffuse and multifocal tumors. No published report to date has described effective pre- or post-operative adjuvant treatment for this disease. In this report, we present the first case of HEHE effectively managed with chemoembolization follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
(35 reference statements)
0
13
1
4
Order By: Relevance
“…In case of metastatic HEHE after OLT, IFN therapy may result in palliation of symptoms and tumor reduction but may also precipitate graft rejection [29]. Chemoembolization followed by OLT can also be effective in the management of HEHE [30]. Furthermore, Furui et al [14] reported five cases of diffuse HEHE without extrahepatic metastasis treated with intra-arterial chemotherapy or transarterial chemoembolization using mitomycin and adriamycin or 5-fluorouracil.…”
Section: Discussionmentioning
confidence: 99%
“…In case of metastatic HEHE after OLT, IFN therapy may result in palliation of symptoms and tumor reduction but may also precipitate graft rejection [29]. Chemoembolization followed by OLT can also be effective in the management of HEHE [30]. Furthermore, Furui et al [14] reported five cases of diffuse HEHE without extrahepatic metastasis treated with intra-arterial chemotherapy or transarterial chemoembolization using mitomycin and adriamycin or 5-fluorouracil.…”
Section: Discussionmentioning
confidence: 99%
“…Auf fal lend ist je doch die Ge fäß neu bildung mit dem Nach weis in tra vas ku lär ge le ge ner Ery thro zy ten. d Der Tu mor zeig te eine Lymphge fäßin va si on in ner halb ei nes Por tal fel des und bei uns und an de ren eine kla re Di agno se pri mär nicht ge stellt wer den konn te [33], wer den die se Pa ti en ten prak tisch immer mit mo der nen Schnitt bild ver fah ren (Com pu ter to mo gra phie, Ma gne tre so nanzto mo gra phie) un ter sucht. Hier bei wer den die oft mul ti plen, so li den Le ber ver än derun gen so wohl als Me tas ta sen wie auch als ver schie de ne For men he pa to zel lu lä rer oder cho lan gio zel lu lä rer Kar zi no me di agnos ti ziert [13,37].…”
Section: Ag No Seunclassified
“…Wie die meis ten an de ren Au to ren sind wir der Mei nung, dass eine de fi ni ti ve Di ag nose nur mit tels der his to lo gi schen Un ter suchung ei ner Tu mor bi op sie ge won nen werden kann [8,19,21,30,32,33]. Al ler dings ist auch die pa t ho his to lo gi sche Di ag no se schwie rig, und Fehl di ag no sen sind häu fig [9,27].…”
Section: Ag No Seunclassified
See 2 more Smart Citations